Secondary Data Analysis of ENETS Survey: Different Age Workers have Different Priorities When Evaluating Life Satisfaction - Nora Gray-Gariazzo PhD; Gonzalo Martínez-Zelaya PhD; M Angeles Bilbaoz PhD (SAGE Publishing, 2023)
Do factors impacting life satisfaction remain stable, or do they change, during the life course of workers? This study analyses the relationships between life satisfaction and age. This study is a secondary analysis of data from ENETS a health and working conditions survey. Workers were grouped into 5 age ranges. A scale of life satisfaction was analyzed, investigating aspects such as income, level of debt, physical and mental health, among others. The confirmatory factor analysis (CFA) showed that 4 of the 5 age ranges have a unifactorial structure, but for those under 30 years of age, 2 factors associated with "psychophysical well-being" and "material well-being" were identified. Thus, at different stages of productive life different priorities affect life satisfaction, this should be considered to optimize the human resources management.